Intermittent resistance exercise and obesity, considered separately or combined, impair spermatic parameters in adult male Wistar rats - Franco Punhagui, Ana Paula; Teixeira, Giovana Rampazzo [UNESP]; Freitas, Marcelo Conrado de [UNESP]; Seraphim, Patricia Monteiro [UNESP]; Alves Fernandes, Glaura Scantamburlo (Wiley-Blackwell, 2018)
Obesity and absence of physical exercise are global problems that affect concentration and sperm quality in the male reproductive system. The purpose of this study was to examine the effect of obesity and resistance training, considered separately or in association, on testicular function and reproductive capacity. Twenty pubertal male Wistar rats were distributed into four groups: control (C) and exercise (E) groups that received standard rat chow; and obese (O) and obese with exercise (OE) groups that received a high-fat diet. All the groups received filtered water during the experimental conditions. Groups E and OE were submitted to 8 weeks of high-intensity intermittent training. Afterwards, testes were collected for sperm count, spermatogenic kinetics, histopathology, morphometry and immunodetection of androgen receptors (AR). The vas deferens was collected for sperm morphology. The results showed that obesity increased body weight, naso-anal length, liver and epididymal fat weight, abnormal spermatozoa and immunodetectable AR. Intermittent exercise decreased daily sperm production (DSP), sperm count and normal spermatozoa, whereas the number of tubules with immunodetectable AR increased. The combination of obesity and intermittent training led to reduced sperm count and DSP, although abnormal spermatozoa and the number of tubules with immunodetectable AR increased. Thus, in conclusion, both obesity and resistance training impaired testicular function during puberty in rats; and this type of exercise has also been shown to be detrimental to testicular physiology.
Keywords: androgen receptor; intermittent resistance exercise; obesity; testis